2021
DOI: 10.1590/1806-93042021000200016
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Regressive Integrated Moving Average Model (ARIMA): conceptual and methodological aspects and applicability in infant mortality

Abstract: This reflective theoretical article, aims to discuss conceptual and methodological aspects about the applications of time series modeling, in particular, the Integrated Auto-regressive Moving Average model and its applicability in infant mortality. This modeling makes it possible to predict future values using past data, outlining and estimating possible scenarios of the health event, highlighting its magnitude. Due to the persistence of infant mortality as a public health problem, the applicability of this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
5
0
5
Order By: Relevance
“…The AR part involves using past data points to predict future ones, the I component includes differentiating the data to achieve stationarity, and the MA aspect uses past forecast errors in the prediction model. This model is particularly effective in applications offering a cost-effective tool for planning and decision-making (Silva et al, 2021). The components of ARIMA are described as follows:…”
Section: Arima Modelling In Economic Forecastingmentioning
confidence: 99%
See 2 more Smart Citations
“…The AR part involves using past data points to predict future ones, the I component includes differentiating the data to achieve stationarity, and the MA aspect uses past forecast errors in the prediction model. This model is particularly effective in applications offering a cost-effective tool for planning and decision-making (Silva et al, 2021). The components of ARIMA are described as follows:…”
Section: Arima Modelling In Economic Forecastingmentioning
confidence: 99%
“…ARIMA modelling for forecasting the National Consumer Price Index (NCPI) in Nepal is a powerful instrument for deciphering and projecting inflationary patterns (Yunus et al, 2015). Despite its complexity and the need for meticulous consideration of multiple factors, this method plays a crucial role in aiding economic planning and policy development (Silva et al, 2021). The efficacy of the ARIMA model is contingent upon the precision of the data used, the stability of the economic environment, and the correctness in the specification of the model parameters (Singh et al, 2020).…”
Section: Arima Modeling and Forecasting Of National Consumer Price In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing temporal behavior and making predictions regarding infant mortality or its components is a tool with great potential in the field of public health, as it allows knowing the behavior of the phenomenon in question over time, therefore supporting decision making ( 15 ) . Different studies recognize the applicability of temporal analysis in understanding infant mortality ( 15 - 16 ) . A study conducted in the state of São Paulo showed a prospect of a drop in infant mortality in the period from 1996 to 2016 ( 16 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Analizar el comportamiento temporal y realizar predicciones acerca de la mortalidad infantil o sus componentes es una herramienta con gran potencial en el campo de la salud pública, ya que permite conocer el comportamiento del fenómeno en cuestión en el tiempo, contribuyendo a la toma de decisiones (15) . Diferentes estudios reconocen la aplicabilidad del análisis temporal en la comprensión de la mortalidad infantil (15)(16) . Un estudio realizado en el estado de São Paulo mostró una perspectiva de disminución de la mortalidad infantil en el período de 1996 a 2016 (16) .…”
Section: Introductionunclassified